Spinal cord compression due to extramedullary haemopoiesis in myelofibrosis. Issue 5 (May 1994) - Cook, G; Sharp, R A
Abstract : Extramedullary haemopoiesis resulting in spinal cord compression is rare. This report of extramedullary myeloid metaplasia in a patient with myelofibrosis serves to illustrate the value of magnetic resonance imaging (MRI) in the diagnosis and management of good neurological recovery.